Non-associative normed algebras - García, Miguel Cabrera; Palacios, Angel Rodriguez (Cambridge : Cambridge University Press, 2014)
The book interweaves pure algebra, geometry of normed spaces, and complex analysis, and includes a wealth of historical comments, background material, examples and exercises.
Volume 1. The Vidav-Palmer and Gelfand-Naimark theorems.
Includes bibliographical references and index.
Keywords: Banach algebras; Algebra